Influência do sistema adesivo e do tempo para acabamento e polimento sobre a infiltração em restaurações de resina com margens em esmalte - Carlos Marcio Prado Goncalves (1999)
An in vitro study was performed in order to verify the influence of different adhesive systems and finishing and polishing times in relation to marginal micro-leakage in Blacks Class V restorations. A total of 150 human canines and premolars were used, and these were higid, with no enamel fractures, and kept in Timols saline solution (0.9%) at 4°C until used. The teeth were randomly divided into three groups with 50 teeth in each, according to the adhesive system used (Single Bond®, Etch & Prime® and SBMP®). Each group was further divided according to the time between the end of the restoration and the finishing and polishing, into five sub-groups: immediately, 24 hours, 14 days, 21 days and 30 days after. The cavity preparations had the tooth/cavity limit totally on enamel, and the following dimensions: mesio/distal 4.0 mm; occlusal/cervical 3.0 mm; and the depth of 2.0 mm. The cavities were prepared using a high-speed drill with a diamond bur, under air/water cooling. Until the cavity preparation, the teeth were kept in distilled water at room temperature. The Z-100® filling composite was used with the Single Bond® and SBMP® systems, while the Degufill® was used with the Etch & Prime® adhesive system. The insertion technique used three diagonal increments, each photo activated twice (40 seconds each). The first activation was kept more distant using an appropriate device in order to reduce the initial light intensity (around 50%). The teeth were sealed, term cycled (500 cycles), submerged in basic fuccin at 0.5% for 24 hours, washed, embedded in polyester resin, sectioned and evaluated in relation to micro-leakage under a stereomicroscope with a 25x magnification, according to a score. The results were statistically analysed with a non-parametric test (Kruskal-Wallis), with the significance level at 5% (p<0.05). Some samples were evaluated under a surface electron microscope. A great number of cohesive enamel fractures were noted in the cavities filled with the Z-100®, in all time periods evaluated. After the results analysis it could be concluded that, under the conditions tested in this study: 1) no adhesive system could effectively avoid the penetration of the die, in any of the periods analyzed; 2) the process of sorption of fluids by the filling composites reduced the micro-leakage values over time; 3)the adhesives systems Single Bond® and SBMP were more effective in the reduction of the micro-leakage than the system Etch & Prime®.